Study the efficacy of platelet rich plasma and local corticosteroid injection for treatment of chronic plantar fasciitis - Borgohain, Munin; Phukon, Raskin (International Journal of Research in Orthopaedics, 2020)
Background: Plantar fasciitis is one of the most common causes of heel pain. Various methods of treatment are available but no ideal treatment has been defined in literature. Corticosteroid (CS) injections are being used as a gold standard but studies have shown its short-term effects and various complications. Recently, platelet rich plasma (PRP) has been advocated as a newer treatment option. The main aim and objective of this study is to compare the two modalities of treatment regarding both pain and functional scores and their complications. Methods: This study was a prospective cohort study. Total 90 patients with chronic plantar fasciitis visiting orthopaedic outpatient department of Assam Medical College and Hospital, Dibrugarh from July 2018 to June 2019 were enrolled for the study after clearance from Institutional Ethics Committee and equally divided into two groups. Group A received PRP and Group B received CS injections. They were assessed with visual analogue scale (VAS) and foot and ankle ability measure (FAAM) score at day 0, at 1 month, 3 months and 6 months. Level of significance was set at p<0.05. Results: The score on VAS and FAAM improved from baseline for both the groups. CS showed better results at 1 month and 3 months but at 6 months, results of PRP were better. 3 patients had recurrences in CS group. Conclusions: Corticosteroid injections provide immediate and short-term relief but PRP is beneficial with long term effects and without any complications.